2019
DOI: 10.1590/1678-4685-gmb-2017-0339
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression levels of Syntaxin 1A and Synaptobrevin 2/Vesicle-Associated Membrane Protein-2 are associated with the progression of bladder cancer

Abstract: Gene expression is tightly regulated in time and space through a multitude of factors consisting of signaling molecules. Soluble N-ethylmaleimide-sensitive-factor attachment protein receptors (SNARE) are membrane proteins responsible for the intercellular trafficking of signals through endocytosis and exocytosis of vesicles. Altered expression of SNARE proteins in cellular communication is the major hallmark of cancer phenotypes as indicated in recent studies. SNAREs play an important role in maintaining cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…several types of cancers including prostate cancer, bladder cancer and papillary renal cell carcinoma (Peak et al 2019(Peak et al , 2020Raja et al 2019). STXBP1 is previously reported to regulate the assemble of SNARE, which is the main machinery for secretion.…”
Section: Discussionmentioning
confidence: 99%
“…several types of cancers including prostate cancer, bladder cancer and papillary renal cell carcinoma (Peak et al 2019(Peak et al , 2020Raja et al 2019). STXBP1 is previously reported to regulate the assemble of SNARE, which is the main machinery for secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, VAMP3 has been reported to be involved in CXCL6 and TNF-a release from the synovial sarcoma cell line SW982, indicating an active role of VAMP proteins in diffusible mediator secretion from cancer cells (80). Furthermore, studies have reported enhanced expression of V-SNARE and t-SNARE members in cancer cells along the course of tumor progression, which may further promote the exocytic release of the mediators in the TME (81).…”
Section: Exocytic Trafficking Pathwaysmentioning
confidence: 99%
“…In order to detect the functions and applications of these closest neighbors of the CHGA, literature verifications were performed. We searched relevant published papers from PubMed and Google scholar concerning these nearby proteins and cancers, and found that SCG3 was convinced as a prognostic biomarker for lung cancer [35] and rectal cancer [36]; SST expression was reported to have a strong relationship with advanced CRC [37]; NCAM1 was correlated with several human cancers [38]; ENO2 were predicted as treatment biomarker for acute lymphoblastic leukemia [39]; SYT1 expression was a candidate colon cancer biomarker [40]; STAX1 was proved to be associated with the transformation of high-grade tumors in the bladder cancer [41]; and as a paralog for CHGA, CHGB was a prognostic marker for the pancreatic neuroendocrine tumors [21]. Expression of SLC22A8 was considered as a valuable biomarker for the lung cancer treatment [42].…”
Section: Discussionmentioning
confidence: 99%